DAMPAK EKOWISATA KAWAH PUTIH DI KECAMATAN RANCABALI BANDUNG TERHADAP SOSIO-EKONOMI MASYARAKAT DAN LINGKUNGAN SERTA STRATEGI PENGEMBANGANNYA - Hendri, Jajang; Sudiana Mahendra, Made; Rai, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2024)
The high perception of Kawah Putih Ecotourism management in involving the community in economic activities still has no impact on increasing people's income and standard of living, so it is necessary to analyze the impact of Kawah Putih Ecotourism development on the socio-economy and environment of the surrounding community and its development strategy. First, it is measured with ecotourism parameters for implementation to determine the economic impact on society which is analyzed with income inequality and Klassen typology. Social impact analyzes its positive and negative impacts. The physical environment is analyzed through environmental awareness parameters and development strategies using IFE-EFE, SWOT and QSPM techniques. The results of the research evaluating the application of the principles and criteria of Crater Ecotourism obtained quite high performance results. While the economic analysis of the average per capita income of the community is relatively small for economic growth, the classification of the Klassen typology of the Kawah Putih community is still considered a disadvantaged area. The social impact of the community is categorized as moderate with a slightly larger percentage of negative impact. The level of environmental awareness is still felt to be quite high. Kawah Putih ecotourism priority strategy is to implement quality and licensed management and services by prioritizing honesty, hospitality, comfort and cleanliness to create tourist loyalty so as to improve the economy, social community is more inclined to positive impacts with high environmental awareness. Keywords: Ecotourism, Socio-Economic, Environmental, Development Strategy